2022
DOI: 10.1021/acsnano.2c08581
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Catalytic Kinetics of Polysulfide Redox Reactions on Transition Metal Compounds in Li–S Batteries

Abstract: Because of their high energy density, low cost, and environmental friendliness, lithium−sulfur (Li−S) batteries are one of the potential candidates for the next-generation energy-storage devices. However, they have been troubled by sluggish reaction kinetics for the insoluble Li 2 S product and capacity degradation because of the severe shuttle effect of polysulfides. These problems have been overcome by introducing transition metal compounds (TMCs) as catalysts into the interlayer of modified separator or sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
86
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 189 publications
(86 citation statements)
references
References 194 publications
(298 reference statements)
0
86
0
Order By: Relevance
“…Polar metal compounds including metal oxides, metal sulfides, metal selenides, metal nitrides, metal borides and metal phosphides have been considered as effective electrocatalysts to accelerate reaction kinetics of LiPSs [200][201][202]. In 2022, Yang et al obtained N-doped Ti 3 C 2 T x MXene-CoS 2 heterostructure (N-MX-CoS 2 ) via CoCl 2 etching and subsequent in-situ sulfidation treatment with thiourea as sulfur source (Fig.…”
Section: Lithium-sulfur Batteriesmentioning
confidence: 99%
“…Polar metal compounds including metal oxides, metal sulfides, metal selenides, metal nitrides, metal borides and metal phosphides have been considered as effective electrocatalysts to accelerate reaction kinetics of LiPSs [200][201][202]. In 2022, Yang et al obtained N-doped Ti 3 C 2 T x MXene-CoS 2 heterostructure (N-MX-CoS 2 ) via CoCl 2 etching and subsequent in-situ sulfidation treatment with thiourea as sulfur source (Fig.…”
Section: Lithium-sulfur Batteriesmentioning
confidence: 99%
“…Some studies have shown that the unoccupied d ‐orbitals of transition metal cations are intrinsically active sites for charge transfer and heterogeneous redox reactions. [ 8d,9 ] It's revealed that transition metal compounds with the unoccupied d ‐orbitals of transition metal cations [ 9a ] matched with the p ‐orbitals of non‐metal anions [ 6b ] at the atomic or molecular level enable active metal center of d/p ‐orbital more advantageous than p ‐orbital hybridization with polysulfide. Hence, the transition metal compounds with these specific structures can greatly improve the conversion kinetics of polysulfides and efficiently suppress the growth of lithium dendrites.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2b,4 ] This is mainly attributed to their unique polar characters, metallic features and tunable electronic configurations. [ 4a ] Several effective routes, including the construction of heterostructures, [ 5 ] surface oxidation/vulcanization, [ 6 ] Schottky junctions, [ 7 ] etc., have been reported to tailor the structures of TMPs‐based electrodes. The interactions between the surfaces/interfaces of TMPs and polysulfide/Li flux have been greatly enhanced during these processes, leading to improved performances.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 During the reaction process, the positive electrode of the Li–S battery is converted between sulfur and LiPSs according to the electrochemical reaction formula S 8 + 16Li ⇆ 8Li 2 S. 3 Unfortunately, there are some problems with Li–S batteries: (i) the low conductivity of the reactive sulfur substances and the discharge product Li 2 S lead to slow redox reaction kinetics and a low sulfur utilization ratio, 4 (ii) the huge volume expansion of the cathode and the notorious formation of anode Li dendrites can decrease the long-term stability and cycle life of the batteries, 5 and (iii) the shuttle effect can induce a loss of lithium polysulfides (LiPSs), corrosion of the lithium anode and reduction in coulombic efficiency (CE). 6…”
mentioning
confidence: 99%